Layered oxides supported Co-Fe bimetal catalyst for carbamazepine degradation via the catalytic activation of peroxymonosulfate - Sun, Qing-Ting (2022)
Co-based catalysts can effectively active peroxymonosulfate (PMS) for organic pollutants degradation. However, the loaded Co on porous materials could easily release into the solution during the reaction. Herein, a stable layered double oxide (LDO)-supported Co-Fe bimetal catalyst, i.e., Co2FeAl-LDO, was synthesized and used to activate PMS for the degradation of carbamazepine (CBZ, a representative pharmaceutical and personal care product). Results show that Co2FeAl-LDO/PMS exhibited high removal of CBZ (>99%) in 30 min with the reaction rate constant (kobs) of 0.2103 min−1. The high activity of Co2FeAl-LDO could be caused by the specific structure of the LDO and the synergistic effect of Co, Fe, and Al on the catalyst. The high CBZ removal (88%) at the fifth run of Co2FeAl-LDO and the low cobalt release (0.4 mg/L) indicate the high stability of Co2FeAl-LDO. The activation and CBZ degradation mechanisms in this highly efficient system were proposed and validated by identifying the radicals and intermediates of CBZ and comparing the active sites on fresh and used Co2FeAl-LDO. pH had a significant effect on CBZ degradation. CoOH+ and HSO5− were the predominant species involved in CBZ degradation under the optimal pH 6.0. The anions and humic acid (HA) inhibited CBZ degradation as they occupied the active sites of the catalyst. This work provides a new substrate to stabilize the active components, and vital information on the synergistic effect of active components during PMS activation.